Psychological competitive abilities of Japanese Olympians: a case of 2002 Salt Lake City and 2006 Torino Winter Games - Tachiya, Y.; Imai, Y.; Yamazaki, F.; Sugo, T.; Hiraki, T.; Hirata, D.; Ishii, M.; Matshuo, A. (Japanese Journal of Elite Sports Support, 2009)
The purpose of this study was to investigate the psychological competitive abilities of Japanese Winter Olympians who participated in the 2002 Salt Lake City (SLC) and 2006 Torino (TR) games. Diagnostic Inventory for Psychological Competitive Ability (DIPCA.3) was utilized, which was developed by Tokunaga and Hashimoto (1988). The inventory consisted of 52 questions, categorized into 12 factors: patience, aggressiveness, volition for self-realization, volition for winning, self-control, ability to relax, concentration, confidence, decisiveness, predictive ability, judgment, and cooperation. The greatest value of each factor was 20 and the greatest achievable total score was 240. The sample size of the Japanese SLC Olympians was 104 (male=56, female=48, mean age=25.0?3.98), and the TR Olympic participants was 111 (male=60, female=51, mean age= 25.4+-4.93).